Students’ extracurricular activities programmes: Prospects and challenges in Arabian Gulf Cooperation Council (GCC)universities (Journal of Student Affairs in Africa, 2025)
AbstractThis paper introduces the prospects enjoyed and anticipated challenges faced by the student extracurricular activities programs in some of the Gulf Cooperation Council (GCC) universities. Limited data and relatively little research on such programs exist, and little reliable information is available on the websites of some of the national universities in the GCC region. For this reason, the study restricted itself to examining two institutions—Qatar University and Sultan Qaboos University in Sultanate of Oman—as case studies. These two universities were chosen due to their significant engagement in student extracurricular activities and their substantial students enrollment numbers. Indeed, the student extracurricular activities program is a growing section in some GCC universities, with different orientations, concentrations on, and comparative advantages to be found among them. Nonetheless, these programs may face several expected challenges within the GCC setting due to the disparities in rules, practices, and objectives across different universities. Quest. 1: In what ways are Qatar University and Sultan Qaboos University in the GCC region effectively integrating their extracurricular activities programs as essential components of educational and developmental policy?  Quest. 2: What motivates Qatar University and Sultan Qaboos University to engage in student extracurricular activities programs?  Quest 3: What challenges are expected to confront these programs at the two universities?Addressing these study concerns necessitates an explanation of the policies and practices that are forming and impacting the development of the student extracurricular activities program as a valuable initiative. Keywords: University student extracurricular activities, Gulf Cooperation Council (GCC), student organization, theory of student involvement
Keywords: University student extracurricular activities; Gulf Cooperation Council (GCC); student organisation; theory of student involvement